Identifying barriers to HIV testing: personal and contextual factors associated with late HIV testing - Schwarcz, Sandra; Richards, T. Anne; Frank, Heidi; Wenzel, Conrad; Chin Hsu, Ling; Chin, Chi-Sheng Jennie; Murphy, Jessie; Dilley, James (AIDS care, 2011)
Late diagnosis of HIV is associated with increased morbidity, mortality, and health care costs. Despite the availability of HIV testing, persons continue to test late in the course of HIV infection. We used the HIV/AIDS case registry of San Francisco Department of Public Health to identify and recruit 41 persons who developed AIDS within 12 months of their HIV diagnosis to participate in a qualitative and quantitative interview regarding late diagnosis of HIV. Thirty-one of the participants were diagnosed with HIV because of symptomatic disease and 50% of the participants were diagnosed with HIV and AIDS concurrently. Half of the subjects had not been tested for HIV prior to diagnosis. Fear was the most frequently cited barrier to testing. Other barriers included being unaware of improved HIV treatment, free/low cost care, and risk for HIV. Recommendations for health care providers to increase early diagnosis of HIV include routine ascertainment of HIV risk behaviors and testing histories, stronger recommendations for patients to be tested, and incorporating testing into routine medical care. Public health messages to increase testing include publicizing that (1) effective, tolerable, and low cost/free care for HIV is readily available, (2) early diagnosis of HIV improves health outcomes, (3) HIV can be transmitted to persons who engage in unprotected oral and insertive anal sex and unprotected receptive anal intercourse without ejaculation and from HIV-infected persons whose infection is well-controlled with antiretroviral therapy, (4) persons who may be infected based upon these behaviors should be tested following exposure, (5) HIV testing information will be kept private, and (6) encouraging friends and family to get HIV tested is beneficial.